1885 Nev. Gen. Stat. 1077, An Act to prohibit the carrying of concealed weapons by minors, § 1 - (:unkn) unknown (General Publisher, 1881)
Prohibited a minor under the age of 21 from carrying a concealed dirk, pistol, sword in case, slungshot, or other dangerous or deadly weapon. Punishable by fine of $20-200 and/or imprisonment of 30 days to 6 months.
--
Keywords: CARRY - CONCEALED - MINORS